Hubungan Anemia dan Preeklampsia dengan Kejadian BBLR di Puskesmas Pembantu Kalibaru Cilincing Jakarta Utara - Afriani, Sinta; Sutarno, Maryati (Universitas Malahayati, 2025)
ABSTRACT LBW babies have a 20 times greater risk of death compared to babies born with normal weight. Factors causing LBW include pregnant women, preeclampsia, anemia. The prevalence of LBW at Kalibaru Sub-district Health Center will still be quite high in 2023 at 3.2%. To study the relationship between anemia and preeclampsia and the incidence of LBW at the Kalibaru Cilincing Sub-Public Health Center, North Jakarta in 2024. Analytical survey, with a cross sectional approach, the population in this study were all babies born at the Kalibaru Cilincing Sub-district Health Center, North Jakarta from January to September 2024, totaling 670 newborns, with a random sampling technique with a sample size of 87 respondents, using The data is secondary data with checklist sheets, univariate and bivariate analysis techniques. From the results of the Chi Square statistical test, it is known that there is a relationship between anemia (ρ value = 0.022 and OR=3.753) and preeclampsia (ρ value = 0.001, and OR value=6.045) with the incidence of LBW at the Kalibaru Cilincing Sub-Public Health Center, North Jakarta in 2024. it is hoped that health workers can provide priority services to pregnant women who have been diagnosed with preeclampsia and anemia, although up to now the Kalibaru Pustu has always provided referrals to pregnant women who have anemia and preeclampsia. It seems that monitoring must be carried out every month regarding the development of these pregnant women, thus LBW births can be avoided. Keywords: Anemia, Preeclampsia, LBW ABSTRAK Bayi BBLR mengalami risiko kematian 20 kali lebih besar dibandingkan dengan bayi yang lahir dengan berat badan normal. Faktor penyebab terjadinya BBLR antara lain ibu hamil preeklamsia, anemia. Prevalasni BBLR di Puskesmas Pembantu Kalibaru masih cukup tinggi pada tahun 2023 sebanyak 3,2%. Untuk mempelajari hubungan antara anemia dan preeklampsia dengan kejadian BBLR di Puskesmas Pembantu Kalibaru Cilincing Jakarta Utara Tahun 2024. Survei Analitik, dengan pendekatan secara cross sectional, populasi dalam penelitian ini seluruh bayi lahir di Puskesmas Pembantu Kalibaru Cilincing Jakarta Utara dari bulan Januari s/d September 2024 sebanyak 670 bayi baru lahir, dengan teknik random samplling dengan jumlah sample 87 responden, memakai data yaitu data seknder dengan lembar cheklist, teknik analisis univariat dan bivariat. Dari hasil uji statsitik uji Chi Square diketahui Ada hubungan anemia (ρ value = 0,022 dan OR=3,753) dan preeklampsia (ρ value = 0,001, dan nilai OR=6,045) dengan kejadian BBLR di Puskesmas Pembantu Kalibaru Cilincing Jakarta Utara Tahun 2024. Diharapkan kepada petugas kesehatan dapat memberikan pelayanan prioritas pada ibu hamil yang sudah terdetekis preeklampsia dan anemia, meskipun selama ini pustu kalibaru selalu memberikan rujukan kepada ibu hamil yang mengalami anemia dan preeklampsia sepertinya harus dilakukan pemantauan setiap bulan mengenai perkembanagna ibu hamil etrsebut, dengan demikian kelahiran dengan BBLR dapat dihindari. Kata Kunci: Anemia, Preeklampsia, BBLR.